2020
DOI: 10.21462/jeltl.v5i1.379
|View full text |Cite
|
Sign up to set email alerts
|

English Language Education Students Perceptions of Self Efficacy in Public Speaking Class

Abstract: <em>Self-efficacy is one of the most pivotal springboards determining EFL learners’ success in acquiring the target language in the communicative classroom contexts. Therefore, well-planned learning strategies and enjoyable learning environments should be provided continuously in order to breed proficient communicators in the target language. To do so, English language teachers need to shift their roles from instructors as facilitators facilitators to nurture EFL learners’ self-efficacy development conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Self-efficacy had the ability to uniquely explain 16.8% of the variance in WTC scores. This finding is in line with Karbakhsh and Ahmadi Safa ( 2020), Wijaya and Mbato ( 2020), Kho-Yar , Rafik-Galea, and Kho (2018), Karimi and Abaszadeh (2017) , who reported self-efficacy beliefs as the strongest variable among a set of variables to be able to predict WTC. The findings gained through this research resemble those studies that have found selfconfidence, which is closely related to self-efficacy, to be the most immediate antecedent of L2 WTC (Eddy, 2015; Peng & Woodrow, 2010;MacIntyre & Charos, 1996).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Self-efficacy had the ability to uniquely explain 16.8% of the variance in WTC scores. This finding is in line with Karbakhsh and Ahmadi Safa ( 2020), Wijaya and Mbato ( 2020), Kho-Yar , Rafik-Galea, and Kho (2018), Karimi and Abaszadeh (2017) , who reported self-efficacy beliefs as the strongest variable among a set of variables to be able to predict WTC. The findings gained through this research resemble those studies that have found selfconfidence, which is closely related to self-efficacy, to be the most immediate antecedent of L2 WTC (Eddy, 2015; Peng & Woodrow, 2010;MacIntyre & Charos, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…In line with Wijaya et al (2020), Karbakhsh and Ahmadi Safa (2020) recommend learners to believe in their capabilities (e.g., self-efficacy). They expounded satisfaction of learners' basic psychological needs in relation to willingness to communicate, and selfefficacy, which they believed may play important roles in predicting success in second language through modeling such relation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the fact shows that students' English speaking skill is still below the standard (Harahap & Widiastuty, 2022;Istiqomah, 2017;Nurhayati, 2016;Renaldi, 2020;Sayuri, 2016;Wijaya & Mbato, 2020). The teacher should present an interesting method of teaching to attract the student's interest and motivation in joining the teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%